Bi-layered PLCL/(PLGA/beta-TCP) composite scaffold for osteochondral tissue engineering - Kim, Su Hee; Kim, Soo Hyun; Jung, Youngmee (SAGE PUBLICATIONS LTD, 2015)
There have been many studies published on bi-layered osteochondral scaffolds that can induce tissue ingrowth for cartilage and bone. However, delivering different signals to each tissue effectively and enabling maturation into complex composite tissues remain challenging. In this study, an osteochondral composite scaffold was fabricated by combining a sintering method and a gel pressing method with poly(lactide-co-glycolide), beta-tricalcium phosphate, and poly(lactide-co-caprolactone). The composite scaffold constituted a poly(lactide-co-glycolide)/beta-tricalcium phosphate scaffold, which has osteoconduction activity for bone regeneration, and an elastic poly(lactide-co-caprolactone) scaffold, which has mechano-active properties for cartilage regeneration. To examine mechanical and biological properties, tensile tests, porosimetry, electron microscopy, and in vitro and in vivo experiments were performed. From the results, we confirmed that the scaffold had a homogeneously interconnected porous structure without a skin layer that exhibited exposed bioceramics onto the scaffold surface. Furthermore, it was shown that poly(lactide-co-glycolide)/beta-tricalcium phosphate of the osteochondral composite scaffold improved osteogenic differentiation and bone tissue formation. Also, chondrogenic differentiation of seeded cells was sustained on the highly elastic poly(lactide-co-caprolactone) of the osteochondral composite scaffold, and the amount of chondral extracellular matrix was increased significantly. Consequently, our osteochondral composite scaffolds may have the appropriate physiological and biological properties for regeneration of osteochondral composites.
Keywords: MESENCHYMAL STEM-CELLS; BONE; REGENERATION; DEFECTS; REPAIR; POLY(L-LACTIDE-CO-EPSILON-CAPROLACTONE); RECONSTRUCTION